Políticas de saúde mental no currículo educacional brasileiro: um estudo das legislações vigentes - Nogueira, Joyce Mesquita (2024)
Mental health is a relevant theme for the Brazilian educational context. Its inclusion in the school curriculum was essential for the integral development of students and the promotion of socio-emotional well-being. In this thesis, the aim was to analyze mental health policies directed towards the Brazilian educational and curricular context, in relation to existing legislation. The specific objectives include: mapping legislation related to mental health in the educational context; identifying the challenges for the implementation of these policies in the curriculum; and assessing perspectives for the re-signification of mental health in the school environment. This study employed a qualitative approach, as well as documentary and bibliographic analysis, examining legislation that addresses mental health in education. The theoretical framework presented the historical process of mental health in Brazil, reflections on concepts related to mental health in the educational context, and mapping of legislation related to mental health in the country’s education system. The theoretical foundations for this thesis are based on Gonzalez Rey (1992), Amarante (2013), and Paulo Freire (2019). The analysis revealed that, despite the urgency of the topic, public policies related to mental health are still not treated as a priority in the educational environment, which perpetuates the issue that motivated this research. The findings also indicated that, although there have been advances, significant challenges still hinder the effective implementation of these policies, such as the lack of mental health professionals in the educational environment to support and guide demands. It was concluded that greater commitment from institutions and public authorities is needed for mental health to become a cross-cutting theme in the school curriculum, ensuring the development of an effective culture of psychosocial care in schools